1997
DOI: 10.1177/0148607197021002100
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cholecystokinin to Prevent the Development of Parenteral Nutrition‐Associated Cholestasis

Abstract: Levels of direct bilirubin were lower in the treated compared with the nontreated group. These findings suggest that cholecystokinin prophylaxis in high-risk neonates may help prevent the development of parenteral nutrition-associated cholestasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…Several methods for preventing such hepatic dysfunction have been reported, such as the use of cyclic TPN 13) or the administration of ursodeoxycholic acid, 14) metronidazole, 15) gentamicin, 16) anti-TNF antibody, 17) cholecystokinin, 18,19) glutamine, [20][21][22][23] or steroids and growth hormone. Nevertheless, the problem of hepatic dysfunction in patients receiving TPN has yet to be completely overcome, and the mechanism of TPN-induced hepatic steatosis remains unclear.…”
Section: Role Of Soybean Oil Fat Emulsion In the Pre-vention Of Tpn-imentioning
confidence: 99%
“…Several methods for preventing such hepatic dysfunction have been reported, such as the use of cyclic TPN 13) or the administration of ursodeoxycholic acid, 14) metronidazole, 15) gentamicin, 16) anti-TNF antibody, 17) cholecystokinin, 18,19) glutamine, [20][21][22][23] or steroids and growth hormone. Nevertheless, the problem of hepatic dysfunction in patients receiving TPN has yet to be completely overcome, and the mechanism of TPN-induced hepatic steatosis remains unclear.…”
Section: Role Of Soybean Oil Fat Emulsion In the Pre-vention Of Tpn-imentioning
confidence: 99%
“…However, to date, studies testing prophylactic strategies have not identified a consistently successful method, other than discontinuing the PN, which frequently is not a feasible option. Those studies included prophylactic administration of taurosusodeoxycholic acid, 5 cholecystokinin-octapeptide, 6,7 taurine, 8 phenobarbitol 9 and removing copper and manganese from the PN. 10,11 One problem inherent in any prophylactic strategy in the NICU is accurately predicting which neonates are at highest risk for developing the adverse outcome, so that high-risk patients can be eligible for study while low-risk patients can be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical access to the biliary tree in many critically-ill patients or those with abdominal wall defects like our patient may not be feasible. Cholecystokinin is a gastrointestinal hormone that has been shown to promote choleresis [17,18] , and was suggested in a retrospective cohort study to prevent severe conjugated hyperbilirubinemia (defined as direct bilirubin 6 5.0 mg/dl) [19] . However, a recent large multicenter double-blind, randomized, controlled trial of cholecystokinin-octapeptide in neonates did not show any effect on conjugated bilirubin levels, incidence of biliary sludge or cholelithiasis formation [15] .…”
Section: Discussionmentioning
confidence: 99%